In an era of highly effective treatment, hepatitis C screening of the United States general population should be considered. (24th August 2017) - Younossi, Zobair; Blissett, Deidre; Blissett, Rob; Henry, Linda; Younossi, Youssef; Beckerman, Rachel; Hunt, Sharon
Abstract: Background & Aims: Hepatitis C virus (HCV) treatment with all oral direct acting antiviral agents (DAA's) achieve sustained virologic response (SVR) rates of 98%. Re‐assessment of general US population screening for HCV is imperative. This study compared the cost‐effectiveness (CE) of three HCV screening strategies: screen all (SA), screen Birth Cohort (BCS), and screen high risks (HRS). Methods: Using a previous designed decision‐analytic Markov model, estimations of the natural history of HCV and CE evaluation of the three HCV screening strategies over a lifetime horizon in the US population was undertaken. Based on age and risk status, 16 cohorts were modelled. Health states included: Fibrosis stages 0 to 4, decompensated cirrhosis, hepatocellular carcinoma, LT, post‐LT, and death. The probability of liver disease progression was based on the presence or absence of virus. Treatment was with approved all‐oral DAAs; 86% were assumed to be seen annually by a primary care provider; SVR rates, transition probabilities, utilities, and costs were from the literature. One‐way sensitivity analyses tested the impact of key model drivers. Results: SA cost 272.0 billion [135 279 per patient] and led to 12.19 QALYs per patient. BCS and HRS cost 274.5 billion (136 568 per patient) and 284.5 billion (141 502 per patient) with 11.65 and 11.25 QALYs per patient respectively. Compared to BCS, SA led to an additional 0.54 QALYs per patient and saved 2.59 billion; compared to HRS, SA led to 0.95 additional QALYs per patient and saved 12.5 billion. Conclusions: Screening the entire US population and treating active viraemia was projected as cost‐saving.